2014
DOI: 10.3758/s13414-014-0788-y
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating perceptual integration: uniting response-time- and accuracy-based methodologies

Abstract: This investigation brings together a response-time system identification methodology (e.g., Townsend & Wenger Psychonomic Bulletin & Review 11, 391-418, 2004a) and an accuracy methodology, intended to assess models of integration across stimulus dimensions (features, modalities, etc.) that were proposed by Shaw and colleagues (e.g., Mulligan & Shaw Perception & Psychophysics 28, 471-478, 1980). The goal was to theoretically examine these separate strategies and to apply them conjointly to the same set of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 36 publications
6
41
0
Order By: Relevance
“…1) The limited-capacity parallel-process models developed by Townsend and colleagues (e.g., Eidels et al, 2015;Townsend & Ashby, 1983;Townsend & Eidels, 2011;Townsend & Nozawa, 1995;Townsend & Wenger, 2004a, b) are directly supported by the present results. Wenger & Gibson (2004) found that attentional pre-cues produced a roughly one-third increase in hazard rates for targets in multi-element displays.…”
Section: Empirical Observationssupporting
confidence: 78%
See 1 more Smart Citation
“…1) The limited-capacity parallel-process models developed by Townsend and colleagues (e.g., Eidels et al, 2015;Townsend & Ashby, 1983;Townsend & Eidels, 2011;Townsend & Nozawa, 1995;Townsend & Wenger, 2004a, b) are directly supported by the present results. Wenger & Gibson (2004) found that attentional pre-cues produced a roughly one-third increase in hazard rates for targets in multi-element displays.…”
Section: Empirical Observationssupporting
confidence: 78%
“…Townsend and colleagues have developed a theoretical framework for experimental methods (e.g., Eidels et al, 2015;Townsend & Nozawa, 1995;Townsend & Wenger, 2004a, b), statistical methods (Houpt & Townsend, 2012;Wenger & Gibson, 2004), and empirical support (Godwin et al, 2015;Wenger & Gibson, 2004) for evaluating efficiency and capacity by ratios of the integrated hazard functions for…”
Section: Appendix 1: Evaluating Temporal Processes By Integrated Hazamentioning
confidence: 99%
“…This was particularly so for visual single blocks, and was more evident for the 50 % than for the 75 % group. An overall tendency for faster Btarget-present^than nontarget responses was observed, in accordance with other redundant-target studies (e.g., Eidels, Townsend, Hughes, & Perry, 2015), and these trends were similar in single and dual blocks. However, in contrast to dual blocks, in single blocks the relative disadvantage for nontargets in the 75 % group was larger, even though that group was faster overall.…”
Section: Discussionsupporting
confidence: 90%
“…Then we apply this new approach to simulated data, and conclude by analyzing a data set published by Eidels, Townsend, Hughes, and Perry (2015).…”
Section: Notationmentioning
confidence: 98%
“…In this section we apply the semiparametric Bayesian analysis to the dot detection data reported in Eidels et al (2015) and included in the R package ''sft'' (Houpt, Blaha, McIntire, Havig, & Townsend, 2013). In this experiment, nine observers were asked to detect a dot presented on a computer monitor by pressing a key.…”
Section: Application To a Published Data Setmentioning
confidence: 99%